Debates on agricultural loan waiver schemes in India: myths and realities. Issue 4 (2nd October 2021) - Pathak, Abhijit; Chattopadhyay, Apurba Kumar
ABSTRACT: The agriculture sector in India is marred with several problems, which have resulted in farmers' distress. To address the distress of the farmers, both Central and State Governments of India implemented agricultural debt waiver schemes (ADWRSs) as major policy interventions in recent years. These schemes differ in terms of coverage of the farmers and lending agencies. However, all of them aim to benefit millions of small and marginal farmers of India. The implication and evaluation of these schemes has invited serious criticisms from both policy makers and researchers. It is true that these schemes have created fiscal pressure on the implementing governments. In addition, some degree of corruption has become an integral part of the schemes. However, given the extent of the indebtedness of the farmers, waivers may also be crucial as a temporary measure to mitigate agricultural distress. This paper explores the debate and examines the criticism of the ADWRSs from various quarters. We have found that the majority of arguments against the debt waiver schemes widely accepted amongst bankers, policy makers and even economists are based on perceptions and are not backed by sound economic logic and analysis.